ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PERUSAHAAN BUKALAPAK TAHUN 2020-2023 - Fitriani, Rahma; Manda, Gusganda Suria (Media Mahardhika, 2025)
The purpose of this study was to determine the financial performance of PT Bukalapak.com Tbk in terms of financial ratio analysis. This type of research is descriptive quantitative. The type of data used is the company's annual financial report data for 2020-2023. The secondary data source is the Financial Statements of PT Bukalapak.com Tbk for 2020-2023 from https://www/idx.co.id. The population and sample of this study are the company's financial statements at PT Bukalapak.com Tbk for 2020-2023. By using a horizontal analysis method of financial analysis, which includes liquidity ratios, leverage ratios and profitability ratios. The results showed that PT Bukalapak.com Tbk based on financial ratios, researchers can find out that the leverage ratio produces good performance, while the liquidity and profitability ratios show poor performance.